Conflict-Based Search for Optimal Multi-Agent Path Finding - Sharon, Guni; Stern, Roni; Felner, Ariel; Sturtevant, Nathan (Proceedings of the International Symposium on Combinatorial Search, 2012)
We present a new two-level search algorithm for optimal multi-agent path finding called Conflict Based Search (CBS). At the high level, a search is performed on a tree based on conflicts between agents. At the low level, a search is performed only for a single agent at a time. Experimental results on various problems shows a speedup of up to a full order of magnitude over previous approaches.